EXTERNAL MYOCARDIAL RUPTURE IN ACUTE PHASE OF MYOCARDIAL INFARCTION: CLINICAL AND INSTRUMENTAL PREDICTORS - E. M. Zeltyn’-Abramov; A. E. Radzevich (Российский кардиологический журнал, 2010)
The retrospective univariable and multivariable analyses of 263 medical histories of patients with acute myocardial infarction, AMI (61 cases of external myocardial rupture), identified predictors of myocardial rupture during AMI. Myocardial rupture was more common in primary AMI, among female patients and elderly individuals. Pre-rupture period was characterised by prolonged anginal attack and persistent sinus tachycardia. AMI, complicated by myocardial rupture, was characterized by “early” pathological Q wave (in the absence of thrombolytic therapy); ST segment elevation >5 mm in two or more adjacent leads; prolonged QTc interval; substantial hypokinesis of intact left ventricular (LV) myocardium, combined with LV ejection fraction (EF) <40%; aneurysm deformation of LV chamber; local dyskinesis with involvement of apical LV segments; deceleration time (DT) for early diastolic filling <150 ms. Independent predictors of myocardial rupture included hypokinesis of intact LV myocardium combined with LV EF <40%; involvement of apical LV segments; ST segment elevation >5 mm; prolonged QTc interval; “early” pathological Q wave; primary AMI; and prolonged anginal attack at early AMI stages.